2011
DOI: 10.1111/j.1365-2966.2011.19173.x
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent maser flare around the high-mass young stellar object G353.273+0.641 - I. Data and overview

Abstract: We have performed very long baseline interferometry (VLBI) and single‐dish monitoring of 22‐GHz H2O maser emission from the high‐mass young stellar object G353.273+0.641 with the VLBI Exploration of Radio Astrometry (VERA) and the Tomakamai 11‐m radio telescope. Two maser flares have been detected, separated by almost two years. Frequent VLBI monitoring has revealed that the flare activity has been accompanied by structural change of the prominent shock front traced by H2O maser alignments. We have detected on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
(65 reference statements)
0
16
0
Order By: Relevance
“…In spite of this, Brand et al (2003) reported 15 isolated maser components with accelerations in the range 0.02 to 1.8 km s −1 yr −1 (with equal numbers of positive and negative acceleration) over time spans of 60 to 4600 days. Similarly, Hunter et al (1994) noted an outward acceleration in one of the water maser features associated with W75N of 1.45 km s −1 yr −1 , while Motogi et al (2011) found that two of the spectral feature associated with G 353.273+0.641 underwent synchronised changes in velocity at a rate of ∼-5 km s −1 yr −1 , occurring during a maser flaring period. Caswell (2004) also noted acceleration in the blue-shifted emission of two sources associated with Galactic star forma-tion: G 291.270-0.719 and G 291.284-0.716.…”
Section: Accelerating Feature Associated With Ngc346 Ir1mentioning
confidence: 84%
“…In spite of this, Brand et al (2003) reported 15 isolated maser components with accelerations in the range 0.02 to 1.8 km s −1 yr −1 (with equal numbers of positive and negative acceleration) over time spans of 60 to 4600 days. Similarly, Hunter et al (1994) noted an outward acceleration in one of the water maser features associated with W75N of 1.45 km s −1 yr −1 , while Motogi et al (2011) found that two of the spectral feature associated with G 353.273+0.641 underwent synchronised changes in velocity at a rate of ∼-5 km s −1 yr −1 , occurring during a maser flaring period. Caswell (2004) also noted acceleration in the blue-shifted emission of two sources associated with Galactic star forma-tion: G 291.270-0.719 and G 291.284-0.716.…”
Section: Accelerating Feature Associated With Ngc346 Ir1mentioning
confidence: 84%
“…291.610-0.529 has remained remarkably stable over several decades, as noted by Caswell & Haynes (1987a) from their 1982spectra and earlier comparisons, and continuing through 1988and 2004, 2005into 2011. 1665-MHz emission is dominated by LHCP emission but accompanied by weaker RHCP emission; 1667-MHz emission shows a weaker, equal amplitude, RHCP and LHCP pair of features.…”
mentioning
confidence: 82%
“…This is rather larger than the typical three-dimensional velocity of this maser site (∼100 km s −1 ), and more like that of a radio jet seen in several HMPOs (Curiel et al 2006;Martí, Rodrígues & Reipurth 1998). Motogi et al (2011) has also measured the linear acceleration (5 km s −1 yr −1 ) of two distinct maser clusters (see Motogi et al 2011 in detail). The lower-limit momentum rate required for the acceleration is ∼ 1.1 × 10 −3 M km s −1 yr −1 .…”
Section: Long-term Monitoring Of the H 2 O Masermentioning
confidence: 67%
“…The observed variation is notably intermittent and there are three significant maser flares. Motogi et al (2011) has revealed that these flares are accompanied by spatial varia- tions, which can be explained by episodic shock propagation along the SE-NW direction. The characteristic velocity, which is estimated from the spatial scale of maser distribution (∼100 au) divided by the time interval of three times flares (∼1yr), is ∼500 km s −1 .…”
Section: Long-term Monitoring Of the H 2 O Masermentioning
confidence: 99%